Inflammation Spreading: Negative Spiral Linking Systemic Inflammatory Disorders and Alzheimer’s Disease - Ni, Junjun; Wu, Zhou (Frontiers in Cellular Neuroscience, 2021)
As a physiological response to injury in the internal body organs, inflammation is responsible for removing dangerous stimuli and initiating healing. However, persistent and exaggerative chronic inflammation cause undesirable negative effects in the organs. Inflammation occurring in the brain and spinal cord is known as neuroinflammation, with microglia acting as the central cellular player. There is increasing evidence suggesting that chronic neuroinflammation is the most relevant pathological feature of Alzheimer's disease (AD), regulating other pathological features, such as the accumulation of amyloid beta (Aβ) and hyperphosphorylation of Tau. Systemic inflammatory signals caused by systemic disorders are known to strongly influence neuroinflammation as a consequence of microglial activation, inflammatory mediator production and the recruitment of peripheral immune cells to the brain, resulting in neuronal dysfunction. However, the neuroinflammation-accelerated neuronal dysfunction in AD also influences the functions of peripheral organs. In the present review, we highlight the link between systemic inflammatory disorders and AD, in which inflammation serving as the common explosion. We discuss the molecular mechanisms that govern the crosstalk between systemic inflammation and neuroinflammation. In our view, inflammation spreading indicates a negative spiral between systemic diseases and AD. Therefore, “dampening inflammation” through the inhibition of cathepsin (Cat)B or CatS may be a novel therapeutic approach for delaying the onset of and enacting early intervention for AD.